Secondary and sucrose metabolism regulated by different light quality combinations involved in melon tolerance to powdery mildew - Jing, Xin (Plant physiology and biochemistry : PPB, 2018)
Copyright © 2018 Elsevier Masson SAS. All rights reserved.